Supramolecular Antioxidant Assemblies of Hyperbranched Polyglycerols and Phenols. Issue 23 (15th September 2014) - Pocoví‐Martínez, Salvador; Kemmer‐Jonas, Ulrike; Pérez‐Prieto, Julia; Frey, Holger; Stiriba, Salah‐Eddine
<x xml:space="preserve">Abstract</x> Supramolecular antioxidant complexes are prepared by the non‐covalent assembly of succinic acid‐modified hyperbranched polyglycerols (PGSAs) and tyramine antioxidant compounds. Using this approach, various supramolecular dendritic polymers based on carboxylic acid‐modified hyperbranched polyglycerol with different molecular weights and different numbers of antioxidant phenols are prepared and characterized by FTIR and NMR spectroscopy as well as via dynamic light scattering (DLS). The local phenolic concentration in this supramolecular architecture plays a key role for their enhanced antioxidant capacity, as shown by oxygen radical absorbance capacity assay (ORAC). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>